How to talk to a borderline - Lachkar, Joan. (Brunner-Routledge, 2010)
"In How to Talk to a Borderline, Joan Lachkar introduces Borderline Personality Disorder (BPD) and outlines the challenges and difficulties it presents to clinicians. She expands current understanding of BPD by outlining eight different kinds of borderline personality disorders and how each of these requires specific communication techniques and methods. Case examples are offered throughout the text and in some cases describe the kinds of partners borderlines attract. This book offers new approaches to communicating, working with, and treating borderline personality disorders while integrating more contemporary treatment methods"--Provided by publisher.